Xangai, uma inflexão no fazer urbano chinês - Schultz, Tiago (Universidade de São Paulo. Faculdade de Arquitetura e Urbanismo., 2018)
This article examines the urban management experience of the city of Shanghai since the economic opening of People’s Republic of China in 1978. The urban policies developed in this context can be considered as a set of tools that the Chinese Communist Party applies to the country's urbanization project, to spread the recent Chinese hyper-urbanization phenomenon. This paper addresses this process of forming a new Asian urban model through the production and sale of spectacular images inside the logic of city marketing, understood through processes such as the xintiandization of many neighborhoods in Shanghai and in other Chinese cities, as well as the construction and urban planning of the Pudong area with the goal to sell the idea of modernization in China.